Character Testing Of New Superior Rice Line Through Participatory Plant Breeding Method - Jaenudin Kartahadimaja; Eka Erlinda Syuriani (Jurnal Penelitian Pertanian Terapan, 2022)
Among the superior varieties can be obtained through breeding. The low level of farmer adoption of improved varieties resulting from breeding is partly due to the different preferences of farmers with breeding. The development of specific varieties will be successful through a participatory breeding program that involves breeders, farmers and rice industry players in the selection process for prospective new varieties. The research objective was to analyze and select the quantitative and qualitative characters of 12 new rice lines to produce new superior rice varieties that were more suitable to farmers' tastes. The research in the field was compiled using a Randomized Completely Block Design (RCBD), as a treatment consisting of 12 lines of F11 generation, each treatment was repeated three times. Observations were made on the like and dislike statements of respondents consisting of 20 farmers on the phenotypic character of each line, as well as an assessment of the phenotype acceptance of each line as assessed by the breeders (4 breeders) before harvest following the guidelines (IRRI, 2002) . The results showed that the F3 line had the highest preference value, namely the value of 0.9, meaning that the farmers liked the most. The line with the lowest preference value is the D2 line with a value of -1 (minus one), meaning that it is the least preferred. Based on the phenotype acceptance value of the breeders for each line, three lines had a phenotypic value of 1 or very good value, namely the B4, H1, and H4 lines, while those with a value of 3 or good were eight lines, namely the B2, B3, B7, D2, D3, F3, F4, and L2 lines. One line has a bad phenotype value, namely the K.